2003
DOI: 10.2307/3588216
|View full text |Cite
|
Sign up to set email alerts
|

L2 Vocabulary Learning from Context: Strategies, Knowledge Sources, and Their Relationship with Success in L2 Lexical Inferencing

Abstract: This study examines the use of strategies and knowledge sources in L2 lexical inferencing and their relationship with inferential success. Data consist of introspective and retrospective think-aloud protocols of 21 intermediate ESL learners who attempted to infer new word meanings from context. Analysis reveals that (a) overall, the rate of success was low even when learners used the strategies and knowledge sources they had at their disposal, (b) different strategies contributed differentially to inferencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
201
0
16

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(263 citation statements)
references
References 50 publications
15
201
0
16
Order By: Relevance
“…Fraser's (1999) study, for instance, suggested that 58% of the total strategy use was dedicated to inferencing and Paribakht and Wesche (1999) indicated 80% use of inferencing strategy among students. Also in his study, Nassaji (2003) concluded that "lexical inferencing has been found to be the mostly widely used by L2 learners" (p. 647).…”
Section: Lexical Inferencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Fraser's (1999) study, for instance, suggested that 58% of the total strategy use was dedicated to inferencing and Paribakht and Wesche (1999) indicated 80% use of inferencing strategy among students. Also in his study, Nassaji (2003) concluded that "lexical inferencing has been found to be the mostly widely used by L2 learners" (p. 647).…”
Section: Lexical Inferencingmentioning
confidence: 99%
“…Paribakht (2005) categorizes these factors into two broad categories of contextual and learner-related factors. Based on the previous studies learner-related factors include factors such as learners' previous L2 learning experience (Fraser, 1999;Paribakht & Wesche, 1999,2006), learner's native language (Paribakht, 2005), learners' attention to text details (Frantzen, 2003), learners' depth of vocabulary knowledge (Nassaji, 2003(Nassaji, , 2004Qian, 1998Qian, , 2002Qian, , 2005 learners' sight vocabulary, their background knowledge and topic familiarity (Pulido, 2004(Pulido, , 2007Atef-Vahid, Maftoon & Zahedi, 2013).…”
Section: Factors Influencing Inferencing Successmentioning
confidence: 99%
“…A ll 40 items in the questionnaire were reorganized and classified under 5 d ifferent groups of strategies as eleven statements on memo ry strategies (items1-11), n ine statements on determination strategies (item [12][13][14][15][16][17][18][19][20], six statements on social strategies (items 21-26), nine statements on cognitive strategies (items 27-35), and five statements on metacognitive strategies (items 36-40) (see Table 2). The frequency of use were measured by 5-point likert-scale fro m 1(never) to 5(always).…”
Section: Journal Of Language Teaching and Research 637mentioning
confidence: 99%
“…From the empirical studies performed by Nassaji (2003) and Bengeleil & Paribakht(2004), it is clear that lexical inferencing may not be completely successful or may not guarantee vocabulary gains; however, those researchers still claim that lexical inferencing really has an important positive effect on vocabulary learning.…”
mentioning
confidence: 99%